1990
DOI: 10.1038/344670a0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium entry through stretch-inactivated ion channels in mdx myotubes

Abstract: Recent advances in understanding the molecular basis of human X-linked muscular dystrophies have come from the identification of dystrophin, a cytoskeletal protein associated with the surface membrane. Although there is little or virtually no dystrophin in affected individuals, it is not known how this causes muscle degeneration. One possibility is that the membrane of dystrophic muscle is weakened and becomes leaky to Ca2+. In muscle from mdx mice, an animal model of the human disease, intracellular Ca2+ is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
198
4
7

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(219 citation statements)
references
References 17 publications
10
198
4
7
Order By: Relevance
“…Changes of Ca 2ϩ channel activities or appearance of novel forms of Ca 2ϩ leak channels, notably of stretch-activated Ca 2ϩ channels, have been reported (18,19). In addition, tetrodotoxin-sensitive spontaneous contractile activity of myotubes in culture exacerbates the stimulated Ca 2ϩ increases (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Changes of Ca 2ϩ channel activities or appearance of novel forms of Ca 2ϩ leak channels, notably of stretch-activated Ca 2ϩ channels, have been reported (18,19). In addition, tetrodotoxin-sensitive spontaneous contractile activity of myotubes in culture exacerbates the stimulated Ca 2ϩ increases (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Ca2" entry through leak channels (Fong et al, 1990;Franco & Lansman, 1990) appears to be increased in dystrophin-deficient muscle fibres (Fong et al, 1990) and thereby leads to activation of Ca2"-dependent proteases which in turn would be responsible for muscle necrosis. Therefore, the PDN-induced decrease in Ca2" influx possibly compensates for an enhanced Ca2" entry into dystrophin-deficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…This increase is localized mainly in areas near the sarcolemma and Ca2+ influx mechanisms would thus be implicated (Turner et al, 1991). An enhancement of the open probability of leak channels (Fong et al, 1990), an activation of stretch-sensitive channels (Franco & Lansman, 1990) and/or a fragile and leaky membrane (Hoffman & Schwartz, 1991) would contribute to this phenomenon. Several authors have proposed a correlation between the increased [Ca2+]i and the enhanced protein degradation found in mdx muscle (Turner et al, 1988;McLennan et al, 1991;Kamper & Rodemann, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies (Franco Jr. and Lansman, 1990;Turner et al, 1993;Hopf et al, 1996;De Backer et al, 2002;Blake et al, 2002) have demonstrated the high influx of extracellular calcium through a dystrophin-deficient membrane, which may lead to the activation of calpains and subsequent muscle necrosis or apoptosis along with the inflammation response. Thus, to capture the characteristics of each phase, we further focus on mechanisms related to muscle regeneration and calcium homeostasis.…”
Section: B Discussionmentioning
confidence: 99%